2021
DOI: 10.1055/a-1400-6034
|View full text |Cite
|
Sign up to set email alerts
|

Severe SARS-CoV-2 Infection Inhibits Fibrinolysis Leading to Changes in Viscoelastic Properties of Blood Clot: A Descriptive Study of Fibrinolysis in COVID-19

Abstract: Background: Accumulating evidence indicates towards an association between SARS-CoV-2 infection and procoagulatory state in blood. Thromboelastographic investigations are useful point-of-care devices to assess coagulation and fibrinolysis. Objectives: We investigated the hypothesis that the procoagulatory state in COVID-19 patients is caused by impaired fibrinolysis system. Methods: COVID-19 patients admitted to normal wards or to the intensive care unit (ICU) were included in the study. Whole blood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 36 publications
(43 reference statements)
4
44
0
Order By: Relevance
“…It is well-correlated with the significantly elevated level of Ddimer in the severe but not in moderate patients. Similar to our finding, a recent study also reported an elevated level of PAI-1 in COVID-19 patients [58]. Consistently, another study reported elevated levels of both PIA-1 and tPA in the hospitalized COVID-19 patients.…”
Section: Discussionsupporting
confidence: 92%
“…It is well-correlated with the significantly elevated level of Ddimer in the severe but not in moderate patients. Similar to our finding, a recent study also reported an elevated level of PAI-1 in COVID-19 patients [58]. Consistently, another study reported elevated levels of both PIA-1 and tPA in the hospitalized COVID-19 patients.…”
Section: Discussionsupporting
confidence: 92%
“…High levels of tPA enhanced fibrinolysis and were strongly correlated with mortality. 15 In contrast, in a different cohort a decrease of fibrinolysis was shown in severely infected patients. 16 In another study, the authors showed a strong correlation of plasminogen concentrations with mortality in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 89%
“…We could confirm increased levels of PAI-1 in COIVD-19 patient-samples that indicates the involvement of the plasminogen-plasmin system, however, we saw no prognostic correlation of PAI-1 concentrations with disease severity. 15 Several newly identified blood markers were increased in patients with severe disease (AAT, EN-RAGE, myoglobin, SAP, TIMP-1, vWF, decorin) in addition to analytes, that had already been described (CRP, IL1-ra, IL-8, IL-10, IL-18, MCP-1). 8,11,24 Published multi-omics analysis and our own observations indicate the involvement of diverse factors, that determine the final outcome of COVID-19.…”
Section: Dovepressmentioning
confidence: 95%
“…The ChAdOx1 nCov-19 vector is constructed with a human tissue plasminogen activator signal sequence [173]. This might engender thoughts of some potential coagulation activity given that tissue plasminogen activator circulates in much higher quantitation in the blood of those with COVID-19 infection versus controls [15]. The latter association is much more avid for those patients with worse disease.…”
Section: Thrombotic Events and Covid-19 Vaccinationmentioning
confidence: 99%
“…It should also be conceded that outside of the potential for thrombosis-related antibodies, alterations in platelet functionality have also been observed [13]. These events must also be seen in the context of endothelial injury or altered fibrinolysis otherwise [14][15][16]. Persistence of an anomalous clotting profile in other regards has also been proposed well after acute infections [17].…”
Section: Introductionmentioning
confidence: 99%